Necessity of Management Course for Chemical Engineering - Mohsen Pirdashti; Arezo Ghadi; Nasrin Noorshahi (آموزش مهندسی ایران, 2010)
Chemical engineering is one of the most versatile and largest engineering fields. Chemical engineering graduates have different status based on their area of study and responsibility in society. Since a low level coordinator is recognized as a manager, chemical engineers could benefit from management science for all control processes, leadership, organizing projects, decision making, creativity and innovation, etc. Therefore this paper emphasizes projects necessity of management course for chemical engineering as an obligatory course, which is a basic need for update management.